Differential effects of transient and sustained activation of BDNF‐TrkB signaling. Issue 7 (31st March 2018) - Guo, Wei; Nagappan, Guhan; Lu, Bai
ABSTRACT: Brain‐derived neurotrophic factor (BDNF) serves a pleiotropic role in the central nervous system, ranging from promoting neuronal survival and differentiation during development and synaptic modulation in the adult. An important, yet unanswered question is how BDNF could serve such diverse functions, sometimes in the same cell. At least two modes of BDNF actions have been elucidated so far based on BDNF signaling kinetics and/or the activity status of the responding neurons. Acute and gradual increases in extracellular BDNF concentrations elicit, respectively, transient and sustained activation of TrkB receptor and its downstream signaling, leading to differential molecular and cellular functions. In cultured neurons, sustained TrkB activation promotes neuronal dendritic arborization and spinogenesis, whereas transient TrkB activation facilitates dendritic growth and spine morphogenesis. In hippocampal slices, slow delivery of BDNF facilitates LTP, whereas fast application of BDNF enhances basal synaptic transmission in schaffer collateral synapses. High‐frequency stimulation of neurons converts BDNF‐induced TrkB signaling from a transient to a sustained mode. These initial insights lay the foundation for future investigation of the BDNF‐TrkB pathway, and analogous signaling pathways to gain a comprehensive understanding to enable translational research. © 2018 Wiley Periodicals, Inc. Develop Neurobiol 78: 647–659, 2018